Winter rye does not increase microbial necromass contributions to soil organic carbon in continuous corn silage in North Central US. (September 2020) - West, Jaimie R.; Cates, Anna M.; Ruark, Matthew D.; Deiss, Leonardo; Whitman, Thea; Rui, Yichao
Abstract: There is insufficient evidence for how cover crop-driven changes to the soil microbial community affect soil organic carbon (SOC) accumulation. One mechanism by which enhanced microbial activity can contribute to SOC accrual is through the conversion of plant inputs to microbial biomass and ultimately necromass that may form organo–mineral associations with soil particles. Here we investigated the effects of winter rye as a cover crop and winter rye harvested as a forage double crop on SOC, chemically labile and complex C fractions, microbial necromass biomarkers (amino sugars), and potential extracellular enzyme activities following a seven–year continuous corn silage trial in southern Wisconsin, North Central US. Whereas SOC increased when winter rye was used as a cover crop compared to no cover, there were no changes to SOC when winter rye was harvested as a forage crop. A positive relationship between chemically labile aliphatic soil–C and total SOC indicates that higher SOC stocks may result from persistence of simple compounds rather than chemically complex, aromatic materials. However, the accumulation of microbial necromass, as inferred from amino sugar biomarker concentrations, was largely unaffected by winter rye use, despite a positive relationship between SOC and amino sugar residue concentrations. Greater potential extracellular enzyme activities indicate increased microbial activity with winter rye. Together, these results suggest that despite some microbial stimulation and potential soil health benefits, winter rye did not increase the contribution of microbial necromass to SOC accrual in this seven–year continuous corn silage field trial. Highlights: We investigated how winter rye influences microbial necromass contributions to SOC in continuous corn silage. Winter rye increased SOC, aliphatic C and enzyme activity compared to no cover crop. Microbial necromass biomarkers were unaffected by 7 years of corn-rye cover systems. Correlation of amino sugars, aliphatic C and SOC implies SOC accrues via microbial means. SOC did not increase in rye double crop system, despite large C inputs.